The Role of Job Characteristics in Moderating the Influence of Flexible Work Arrangement and Self-Efficacy on Employee Engagement - Gusti, Zachwa Nugrai; Dewi, Yustina Erti Pravitasmara (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research examines the role of job characteristics in moderating the influence of flexible work arrangements and self-efficacy on employee engagement at PT Desa Wisata Indonesia which aims to provide a deeper understanding of maximizing employee engagement through the application of work flexibility, self-efficacy, and the role of job characteristics so that it can help the organization. in preparing ourselves to face the changes occurring in the world of work. This research uses a quantitative methodology using SPSS with the methodology used including a validity test, reliability test, classical assumption test, t-test, and F test to test the influence of the independent variable on the dependent variable. The research results show that the flexible work arrangement and self-efficacy variables have a positive and significant effect on employee engagement, and the job characteristics variables can moderate the influence of the flexible work arrangement and self-efficacy variables on employee engagement. This research examines the role of job characteristics in moderating the influence of flexible work arrangements and self-efficacy on employee engagement at PT Desa Wisata Indonesia which aims to provide a deeper understanding of maximizing employee engagement through the application of work flexibility, self-efficacy, and the role of job characteristics so that it can help the organization. in preparing ourselves to face the changes occurring in the world of work. This research uses a quantitative methodology using SPSS with the methodology used including a validity test, reliability test, classical assumption test, t-test, and F test to test the influence of the independent variable on the dependent variable. The research results show that the flexible work arrangement and self-efficacy variables have a positive and significant effect on employee engagement, and the job characteristics variables can moderate the influence of the flexible work arrangement and self-efficacy variables on employee engagement.